(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article empirically analyzes the dynamic changes in the structure of tax revenues of the State Budget of the Republic of Uzbekistan during the period 2019–2024. Growth trends in direct taxes, indirect taxes, and resource payments are identified, and their impact on the financial stability of regional budgets is assessed. The analysis shows that total tax revenues increased from 112,165.4 billion soums in 2019 to 274,423 billion soums in 2024, representing a 2.45-fold increase. Value-added tax remains the leading component within indirect taxes. Based on the results, recommendations are developed to improve tax policy and strengthen regional financial independence.